Some issues on Bibliometrics: the way I would like to be helped as a University Professor - Gouveia, Luis Borges (2013)
Apresentação no Workshop “Some issues on Bibliometrics: the way I would like to be helped as a University Professor”, organizado pela Biblioteca da Universidade Fernando Pessoa. O Workshop teve lugar na sala P0.2 e decorreu no dia 04 de dezembro de 2013, entre as 10:00 e as 12:00h.